Electrical Switching Behavior of a [60]Fullerene‐Based Molecular Wire Encapsulated in a Syndiotactic Poly(methyl methacrylate) Helical Cavity1. Issue 3 (13th December 2012) - Qi, Shengli; Iida, Hiroki; Liu, Lili; Irle, Stephan; Hu, Wenping; Yashima, Eiji
<x xml:space="preserve">Abstract</x> Exploding peapods? A helical syndiotactic poly(methyl methacrylate) encapsulates C60 molecules within its helical cavity to form a supramolecular peapod‐like molecular wire. Sandwich devices using these molecular wires in the active layer exhibit an irreversible electrical switching effect. Calculations predict a violent Coulomb explosion in the peapod C60 wires during the charge injection process, which would account for the observed irreversible electrical switching.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>